Postnatal Ablation of Foxm1 from Cardiomyocytes Causes Late Onset Cardiac Hypertrophy and Fibrosis without Exacerbating Pressure Overload-Induced Cardiac Remodeling - Bolte, Craig; Zhang, Yufang; York, Allen; Kalin, Tanya V.; Schultz, Jo El J.; Molkentin, Jeffery D.; Kalinichenko, Vladimir V. (PLOS ONE, 2012)
Heart disease remains a leading cause of morbidity and mortality in the industrialized world. Hypertrophic cardiomyopathy is the most common genetic cardiovascular disorder and the most common cause of sudden cardiac death. Foxm1 transcription factor (also known as HFH-11B, Trident, Win or MPP2) plays an important role in the pathogenesis of various cancers and is a critical mediator of post-injury repair in multiple organs. Foxm1 has been previously shown to be essential for heart development and proliferation of embryonic cardiomyocytes. However, the role of Foxm1 in postnatal heart development and in cardiac injury has not been evaluated. To delete Foxm1 in postnatal cardiomyocytes, αMHC-Cre/Foxm1fl/fl mice were generated. Surprisingly, αMHC-Cre/Foxm1fl/fl mice exhibited normal cardiomyocyte proliferation at postnatal day seven and had no defects in cardiac structure or function but developed cardiac hypertrophy and fibrosis late in life. The development of cardiomyocyte hypertrophy and cardiac fibrosis in aged Foxm1-deficient mice was associated with reduced expression of Hey2, an important regulator of cardiac homeostasis, and increased expression of genes critical for cardiac remodeling, including MMP9, αSMA, fibronectin and vimentin. We also found that following aortic constriction Foxm1 mRNA and protein were induced in cardiomyocytes. However, Foxm1 deletion did not exacerbate cardiac hypertrophy or fibrosis following chronic pressure overload. Our results demonstrate that Foxm1 regulates genes critical for age-induced cardiomyocyte hypertrophy and cardiac fibrosis.